E-Summary Teaching Materials with Hannafin & Peck Models for Training Participants in the Human Resources Development Agency - Pauline Tricia Andriani; I Gde Wawan Sudatha; I Kadek Suartama (Universitas Pendidikan Ganesha, 2021)
This study aims to describe the design of electronic teaching materials packaged in e-summary form, and to determine the validity of e-summary teaching materials according to experts and product trials. This type of research is development research using the Hannafin & Peck model. The types of data in this study are quantitative and qualitative data. The research data collection used the document recording method and the questionnaire method. The data analysis technique used is descriptive quantitative analysis technique, and descriptive qualitative. The results of the study (1) The design of this e-summary teaching material consists of three stages, namely the needs analysis stage, the design stage, the development and implementation stage. And at each stage it passes through the evaluation stage. (2) The validity of the development of e-summary teaching materials is measured through (a) the results of the content/content expert review by obtaining a percentage of 93.3% being in very good qualification, (b) the results of the e-summary linguist review being 87.5% being on good qualifications (c) the results of the review of individual trials show that the percentage of the overall subject is 97.1% with very good qualifications and (d) the results of the small group trial review show that the percentage of the overall subject is 96.3% with very good qualifications. . In general, the research results show that e-summary is valid with very good quality and is suitable for use in the learning process in creative thinking training. Suggestions that can be given from the results of this study are that this e-summary teaching material can be used optimally in the learning process so that it can increase the training participants' self-study motivation and make it easier to understand the training material.